PELAKSANAAN AUDIT OPERASIONAL ATAS KINERJA SDM BAGIAN PEMASARAN PT ASURANSI JASA INDONESIA (Persero) - Rachmaningtyas, Thea Anggun; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to comprehend the implementation process of operational audit and to analyze the factor which influences the performance of human resources on marketing department. The analysis method has been done by using qualitative descriptive method and the data collection technique has been done by conducting observation, interview, and documentation which relevant to the operational audit on the performance of human resources at marketing department of PT Asuransi Jasa Indonesia (Persero) Kantor Cabang Surabaya II. The result of the research shows that the performance of human resources on marketing department of PT Asuransi Jasa Indonesia (Persero) Kantor Cabang Surabaya II has some problems i.e.: the result of premium revenue and the result of product sales of Aneka in 2015 is far from the target that has been determined by the company, the lack of appropriate communication approach with the external party and the lack of human resources on marketing department. The implication of the implementation of operational audit is expected to be able to measure the performance of human resources of marketing department and it can support in taking the right steps for the company.Keywords: Operational Audit, Performance Measurement, Marketing